Differences in root distribution, nutrient acquisition and nutrient utilization by tropical forage species grown in degraded hillside soil conditions - Gómez Carabali, A; Rao, Idupulapati M.; Ricaurte, Jaumer (2010)
Low nutrient availability, especially phosphorus (P) and nitrogen (N) supply is the major limitation to forage production in acid infertile soils of the tropics. A ﬁeld study was conducted at the farm ‘La Es- peranza’ located in Mondomo, Department of Cauca, in the coffee growing zone of Colombia. The main objective was to determine differences in root distribution, nutrient (N, P, K, Ca, Mg and S) acquisition and nutrient utilization of one C4 forage grass (Brachiaria dictyoneura) and two C3 forage legumes (Arachis pintoi and Centrosema macrocarpum) grown under two fertilization levels, cultivated either in monoculture or in association and harvested at four different ages.There were no signiﬁcant differences in root biomass among the grass and legumes and their combinations. The native vegetation had the lowest root biomass; while the introduced grass (B. dictyoneura) had the highest root length density among all materials at all depths and ages and the native vegetation had the highest speciﬁc root length. As expected, nutrient uptake increased with age and with high fertilization in all species. Centrosema macrocarpun had the highest N and Ca uptake among all plant materials tested. Uptake of P, K and Mg was greater in the grass B. dictyoneura than in the other plant species and combination planting at all ages. On the other hand, the grass had the lowest Ca uptake. The grass and its mixture with the legumes A. pintoi and C. macrocarpun had the highest S uptake. A highly signiﬁcant (p<0.001) correlation was found between root length density (depths 0-10 and 10-20 cm) and N and P uptake. Nutrient use efﬁciency (g of forage produced for g of nutrient uptake) increased with age until 38 weeks. At 55 weeks a sharp decline was observed in nutrient use efﬁciency. N, Ca and P use efﬁciency values were higher with the grass than with the two legumes tested. K use efﬁciency was similar among the three species. For Mg and S the grass had the highest values and the legume, A. pintoi the lowest.